Key Factors in Achieving Successful Endoscopic Dissection of Rectal Tumors: Early Results of 33 Consecutive Rectal Endoscopic Submucosal Dissections in Polish Academic Center. Issue 2 (April 2015) - Spychalski, Michal; Zelga, Piotr; Dziki, Adam
Abstract : Introduction: The aim of the study was to investigate outcomes of rectal endoscopic dissection (ESDs) performed in a single academic institution in Poland. Methods and Patients: Thirty-three consecutive cases of rectal ESDs were performed between June 2013 and April 2014. Effectiveness of dissection, complications, and the tumor recurrence after 3 months of treatment were than retrospectively investigated. Results: The average size of the dissected tumor was 4.025 cm. Overall en-block resection rate was 70%. Follow-up examinations after 3 months so far were conducted in 15 patients. There was no local recurrence. In univariate analysis, the en-bloc resection rate was significantly higher in smaller lesions ( P <0.001) and in patients undergone ESD in second half period of service duration. Conclusions: ESD of the rectal tumors is a valuable alternative treatment method for adenomas and T1 SM1 rectal cancers. The risk of serious complications and local recurrence is low.